Sebepercepce trenérů národního volejbalového týmu postižených Self-perception of national team coaches in volleyball for the disabled - Rajko Vute (Palacky University, 2005)
Příspěvek se pokusí odpovědět na základní otázky týkající se trenérů volejbalu pro postižené: jejich sebepercepce, jejich vnímání ideálního trenéra, a statisticky zachytit významnost rozdílů mezi těmito dvěma kategoriemi. Výzkumný vzorek se skládal ze 32 trenérů národních volejbalových týmů tělesně postižených. Data byla shromážděna během Mistrovství Evropy žen ve volejbalu vsedě, Mistrovství Evropy mužů ve volejbalu vsedě a Světového poháru mužů ve volejbalu vestoje. Sběr dat byl dokončen v roce 2003. Inventář CSPL-TT94 (Seznam sebepercepce trenérů) se skládá z 26 položek, týkajících se osobních kvalit trenérů, které jsou důležité pro úspěšné trénování týmů. Sedmibodová stupnice od 0 do 6 umožňuje získat informace o úrovni sebeprecepce trenérů a jejich ideální charakteristiky. Sebepercepce trenérů ukazuje, že silná stránka jejich osobních charakteristik důležitých pro trénování volejbalu pro postižené je v jejich motivaci, zodpovědnosti a sebedůvěře, zatímco charakteristiky jako úzkost, starost, agresivita a individualismus měly nižší bodové hodnocení. Ideální trenér je vynikající v motivaci, zodpovědnosti a sebeovládání s malou úzkostí. Mezi 20 z 26 osobních charakteristik důležitých pro trénování volejbalu pro postižené jsme nalezli statisticky významné rozdíly. Prezentované poznatky jsou významné pro ty, kteří jsou zapojeni v tréninku vrcholových volejbalistů s postižením a pokouší se vytvořit lepší klima sportujícím osobám s postižením. This study attempted to answer the basic questions concerning coaches of volleyball for the disabled: their self-perception, their perception of an ideal coach, and statistically significant differences among those two categories. The research sample consisted of 32 coaches of the national teams in volleyball for the disabled. Data was gathered during the European Championship in Sitting Volleyball for Women, the European Championship in Sitting Volleyball for Men and the World Cup in Standing Volleyball for Men, and were completed in 2003. The CSPL-TT94 List (Coach Self-Perception List, Tušak & Tušak, 1994) consists of 26 items about coaches' personal qualities important for successful coaching. A seven point scale from 0 to 6 was introduced to obtain coaches' level of self-perception and ideal coach characteristics. Coaches' self-perception shows us that the strong side of their personal characteristics important for coaching volleyball for the disabled lies in motivation, responsibility and self-confidence, while the lowest scores belong to anxiety, aggressiveness and individualism. An ideal coach is outstanding in motivation, responsibility and self-control with low scores in anxiety. In twenty out of twenty-six personal characteristics important for coaching volleyball for the disabled, we found statistically important differences. These findings have a particular relevance to those involved in coaching elite athletes in volleyball for the disabled. This paper also tries to promote better understanding of participation in sport for the disabled.